Growing old in Byzantium: the construction of ageing in twelfth-century literary and visual culture - Hitt, J (2023)
Byzantium in the twelfth century was a society in which diverse images of the elderly existed simultaneously. This thesis analyses the multiple meanings of growing old in this period of Byzantine history, painting a nuanced picture of the ideas and associations that underpinned the many conflicting representations of ageing. The results of this study shed some light on the cultural significance of growing old, and on the role of age in the construction of Byzantine identity more generally.